2021
DOI: 10.1016/j.redox.2021.101977
|View full text |Cite|
|
Sign up to set email alerts
|

ent-Kaurane diterpenoids induce apoptosis and ferroptosis through targeting redox resetting to overcome cisplatin resistance

Abstract: Reactive oxygen species (ROS) induction is an effective mechanism to kill cancer cells for many chemotherapeutics, while resettled redox homeostasis induced by the anticancer drugs will promote cancer chemoresistance. Natural ent -kaurane diterpenoids have been found to bind glutathione (GSH) and sulfhydryl group in antioxidant enzymes covalently, which leads to the destruction of intracellular redox homeostasis. Therefore, redox resetting destruction by ent -kaura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 56 publications
(59 reference statements)
0
33
0
Order By: Relevance
“… 11 , 12 Moreover, induction of ferroptosis enhances the therapeutic efficacy of cisplatin in cancer cells. 13 , 14 In the context of PCa, tumor cells are vulnerable to ferroptosis induction, and treatment with the antiandrogen enzalutamide induces lipid peroxidation and leads to sensitivity to GPX4 inhibition and ferroptosis. 4 , 15 Therefore, ferroptosis is closely related to PCa progression, and ferroptosis inducers may be even more potent in combination therapy settings.…”
Section: Introductionmentioning
confidence: 99%
“… 11 , 12 Moreover, induction of ferroptosis enhances the therapeutic efficacy of cisplatin in cancer cells. 13 , 14 In the context of PCa, tumor cells are vulnerable to ferroptosis induction, and treatment with the antiandrogen enzalutamide induces lipid peroxidation and leads to sensitivity to GPX4 inhibition and ferroptosis. 4 , 15 Therefore, ferroptosis is closely related to PCa progression, and ferroptosis inducers may be even more potent in combination therapy settings.…”
Section: Introductionmentioning
confidence: 99%
“…ATF3 (activating transcription factor 3) may induce ferroptosis by blocking the Nrf2/Keap1/xCT signaling pathway and reverse the sensitivity of gastric cancer cells to cisplatin ( Fu D. et al, 2021 ). Ent-Kaurane derivatives are promising in chemotherapy and are capable of reversing the resistance to cisplatin by dual inhibition of PRDX I/II and GSH ( Sun Y. et al, 2021 ). Non-small-cell lung cancer (NSCLC) accounts for approximately 85% of lung cancer cases ( Ferlay et al, 2015 ).…”
Section: Ferroptosis and Drug Resistancementioning
confidence: 99%
“… [ 34 ] Cisplatin Ent-kaurane diterpenoids Glutathione (GSH) Lung cancer Ent-kaurane diterpenoids target peroxiredoxin I/II and block GSH synthesis, thereby inducing ferroptosis and overcoming cisplatin resistance. [ 35 ] Erastin and sulfasalazine Cystine/glutamate antiporter (xCT) Head and neck cancer Erastin and sulfasalazine inhibit the xCT system to induce ferroptosis and overcome cisplatin resistance. [ 36 ] / xCT Gastric cancer Suppressing the Nrf2/Keap1/xCT pathway inhibits xCT system to induce ferroptosis and overcome cisplatin resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, ent-kaurane diterpenoids have been reported to be able to overcome cisplatin resistance by inducing ferroptosis. Further mechanistic studies have revealed that ferroptosis induced by ent-kaurane diterpenoids is caused by targeting peroxiredoxin I/II and depleting GSH [ 35 ]. Cysteine is an essential cellular antioxidant and the rate-limiting amino acid for GSH biosynthesis.…”
Section: Introductionmentioning
confidence: 99%